2015
DOI: 10.1038/bjc.2014.606
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the lifetime risk of developing cancer in Great Britain: comparison of risk for those born from 1930 to 1960

Abstract: Background:Typically, lifetime risk is calculated by the period method using current risks at different ages. Here, we estimate the probability of being diagnosed with cancer for individuals born in a given year, by estimating future risks as the cohort ages.Methods:We estimated the lifetime risk of cancer in Britain separately for men and women born in each year from 1930 to 1960. We projected rates of all cancers (excluding non-melanoma skin cancer) and of all cancer deaths forwards using a flexible age-peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
164
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(172 citation statements)
references
References 10 publications
3
164
2
3
Order By: Relevance
“…The global cancer burden is expected to increase,9 and a recent study from Great Britain has reported the lifetime risk to be 1 in 2 among individuals born since 1960 10. Furthermore, the emotional distress and economic cost of cancers are immense and most likely rising 11.…”
Section: Introductionmentioning
confidence: 99%
“…The global cancer burden is expected to increase,9 and a recent study from Great Britain has reported the lifetime risk to be 1 in 2 among individuals born since 1960 10. Furthermore, the emotional distress and economic cost of cancers are immense and most likely rising 11.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that one in two people in Great Britain will develop some form of cancer during their lifetime [1]. In 2014, 357,000 new cases of cancer were diagnosed in the UK and the rate of incidence is increasing [2].…”
Section: The Use Of Mobile Devices To Help Patients With Cancer To Mementioning
confidence: 99%
“…
The use of mobile devices to help patients with cancer to meet their information needs in non-inpatient settings: A systematic review IntroductionIt is estimated that one in two people in Great Britain will develop some form of cancer during their lifetime [1]. In 2014, 357,000 new cases of cancer were diagnosed in the UK and the rate of incidence is increasing [2].
…”
mentioning
confidence: 99%
“…10 This puts an increasing strain on primary care who play a pivotal role in ensuring patients with suspected cancer receive appropriate referrals. ACE will contribute to the evidence base to inform commissioners and national policy makers about effective approaches to diagnosing patients earlier and, importantly, how to ensure GPs and other healthcare professionals are adequately supported in making decisions about patient care.…”
Section: Streamlining Patient Diagnostic Pathways Via Multidisciplinamentioning
confidence: 99%